Characterization of Uterine Cervix Cancers in Women from Appalachian Kentucky - Kunos, Charles A.; Fabian, Denise; Kudrimoti, Mahesh; Miller, Rachel W.; Ueland, Frederick R.; Randall, Marcus E. (Frontiers in Oncology, 2021)
Uterine cervix cancer (UCCx) is clinically and socioeconomically diverse among women in the United States (US), which obscures the discovery of effective radiochemotherapy approaches for this disease. UCCx afflicts 7.5 per 100,000 American women nationally but 11.7 per 100,000 women in Appalachian Kentucky (AppKY), when age-adjusted to the 2000 US standard population. Epidemiological chart review was performed on 212 women with UCCx treated at the University of Kentucky (UKY) between January 2001 and July 2021. Demographics, tumor characteristics, and relative radiochemotherapy dose and schedule intensity were compared among AppKY and non-AppKY cohorts as well as Surveillance, Epidemiology, and End Results (SEER) data. One hundred thirty-eight (65%) of 212 women seeking radiochemotherapy treatment for UCCx resided in AppKY. Most (80%) sought external-beam radiochemotherapy close to their AppKY residence. Brachytherapy was then most frequently (96%) conducted at UKY. Cancer stage at diagnosis was significantly more advanced in AppKY residents. Women residing in AppKY had a median 10-week radiochemotherapy course, longer than an 8-week guideline. Estimated survival in women residing in AppKY was 8% lower than US national averages. In summary, this study identified an increased percentage of advanced-stage UCCx cancer at diagnosis arising in AppKY residents, with a confounding population-specific delay in radiochemotherapy schedule intensity lowering survival.